Pembuatan Otak Otak Ikan Berbahan Dasar Ikan Cakalang dan Jamur Kuping - Adesca Happy Yonafee; Niken Purwidiani; Any Sutiadiningsih; Sri Handajani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is an experiment in making otak-otak cakalang and ear mushroom as a product innovation. This researcher aims to determine; 1) the results of sensory quality including color, aroma, density, taste, and liking; 2) the content of water content, protein, fat, ash and fiber. This research is an experimental research with a factor pattern of comparison of the amount of ear mushrooms and skipjack with 3 treatments, namely (1:5), (1:3), (1:2) with sensory quality assessment by 5 trained panelists and 35 semi trained. Data analysis using Single Anova (one way). The results showed: 1) The proportion of ear mushroom and skipjack fish affects the aroma, taste, density but has no effect on the color of otak-otak cakalang. Otak-otak cakalang made from skipjack and ear mushrooms produce cream-colored products, savory fish aroma, and have a dense density. Products that are well received by panelists are 100:200 ratio which is the amount of 100 grams of ear mushrooms and 200 grams of tuna and, 2) The nutritional content of otak-otak cakalang shows that it has a content per 100 grams of water content of 28.96%, protein 13.87%, fat 4.51%, ash content 0.31% and fiber 2.35%.